New status for two African giant forest shrews, Crocidura goliath goliath and C. goliath nimbasilvanus (Mammalia: Soricomorpha), based on molecular and geometic morphometric analyses - (:unkn) unknown (My University, 2013)
Crocidura goliath nimbasilvanus Hutterer, 2003 (replacement name for C. odorata guineensis Heim de Balsac, 1968) from West Africa (Guinea, Liberia, Ivory Coast) and Crocidura goliath goliath Thomas, 1906 from Central Africa (Cameroon, Central African Republic, Gabon, Republic of Congo, Democratic Republic of Congo) were regarded as members of a single species until recently. A phylogenetic analysis including three mitochondrial (16S, cytb and COI) and one nuclear marker (BRCA) shows that C. g. nimbasilvanus is the sister taxon of C. nimbae, a species also endemic to West Africa. Crocidura g. goliath is part of the C. olivieri group and closely related to C. olivieri, C. viaria and C. fulvastra. Calculation of genetic distances between cytb sequences confirms this pattern (divergence of 13.5% between C. g. nimbasilvanus and C. g. goliath). An analysis of 112 skulls using morphometric geometrics provides evidence of marked shape differences between the two taxa. Despite close external morphological resemblances, we found diagnostic external and craniodental characters between these two forms. We therefore propose to treat C. nimbasilvanus and C. goliath as distinct species. Similar morphological features exhibited by these two African giant forest shrews, especially their large size, may be the result of homoplasy due to convergent evolutionary pressure. We also investigated the phenotypic diversification in size and skull shape within C. goliath and discovered strong intraspecific variability.
Keywords: African Research